Male Tetrameres Fissispins diesing, 1861 from the domestic indigenous fowl (Gallus donesticus L.) - Lee, C. C.; M., Harisah; Bohari, Y.; Abdullah Sani, Rehana (Persatuan Doktor Veterinar Malaysia, 1986)
Several male worms of Tetrameres fissispina were recovered from the domestic indigenous fowls in a village in Selangor. A brief description of the worm is given.